PtHAK5, a candidate for mediating high-affinity K + uptake in the halophytic grass, Puccinellia tenuiflora - YANG, Haili; ZHANG, Weidan; CHAI, Weiwei; WANG, Wenying; GAO, Li; ZHANG, Jing; WANG, Yongping; WANG, Suo-Min (Frontiers of Agricultural Science and Engineering, 2018)
Puccinellia tenuiflora is a typical salt-exclu-ding halophytic grass with strong salt-tolerance, which enhances tolerance by restricting Na + influx as well as having a strong selectivity for K + over Na +. The HAK5 K + transporters generally modulate effective K + acquisition in plants, especially under low K + condition. In this study, PtHAK5 from P. tenuiflora was isolated by RT-PCR and characterized using yeast complementation. The results showed PtHAK5 consisted of 784 amino acids and shared over 80% homology with the identified high-affinity K + transporter HAK5 from other higher plants. The expression of PtHAK5 rescued the K +-uptake-defective phenotype of yeast strain CY162. In conclusion, PtHAK5 is a candidate for mediating high-affinity K + uptake under low K + conditions.